Novel measures of continental‐scale avian migration phenology related to proximate environmental cues. Issue 9 (26th October 2016) - Kelly, Jeffrey F.; Horton, Kyle G.; Stepanian, Phillip M.; de Beurs, Kirsten M.; Fagin, Todd; Bridge, Eli S.; Chilson, Phillip B.
Abstract: Rapid changes in seasonal avian migrations provide compelling examples of biotic response to climate change. Seasonal waves of land surface phenology and temperature are thought to be primary exogenous cues that migrants use to fine tune migration timing. Exploration of the role that these cues play in regulating migration timing requires better spatial, temporal, and taxonomic sampling than is typically available. We analyze weather surveillance radar (WSR) and eBird citizen science data in an effort to understand the macroscale relationships among migration phenology, seasonal waves of land surface phenology and seasonality of temperature. We demonstrate that both WSR and eBird data provide similar estimates of migration timing at local (within 100 km) and macro scales (>20° of latitude). These measures of avian phenology were positively correlated with spring temperatures and land surface phenology (extended spring index of first leaf date), which followed a south to north wave. Start‐of‐spring, estimated from a remotely sensed index of vegetation greenness, did not show the expected pattern from south to north and appears unlikely to be a useful exogenous migration cue within the study region. Future analyses of WSR and eBird data have the potential to provide high‐resolution phenology data that may be useful in understanding spatiotemporal dynamics of migration systems and the response of these systems to climate change.